Development of Capcut Application-Based Learning Video Media on Fraction Materials for Third Grade Students of Sd Negeri Burengan 2 Kediri City - Ningrum, Niken Probo Setya; Wenda, Dhian Dwi Nur; Wiguna, Frans Aditia (Kirana Publisher (KNPub), 2025)
This research aims to produce Capcut application-based learning videos on fraction materials for third grade students of SDN Burengan 2 Kediri. Development was carried out through the five stages of ADDIE: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were third grade students. The feasibility of the product was tested through three aspects: validity, practicality, and effectiveness, using questionnaires and evaluation questions as data collection methods. The results of media expert validation showed a score of 88% and material expert 89%, both of which were in the very valid category. Practicality test from student questionnaires obtained an average score of 94%, and from teachers 93%, indicating that the media is very practical. The effectiveness test based on evaluation results showed 90% of students scored above average. Thus, this learning video is declared very feasible and can be used in the process of learning math fraction material.